2017
DOI: 10.1002/chem.201700169
|View full text |Cite
|
Sign up to set email alerts
|

Design of Allosteric Stimulators of the Hsp90 ATPase as New Anticancer Leads

Abstract: We rationally designed allosteric compounds that stimulate Hsp90 ATPase activity and show anticancer potencies in the low micromolar to nanomolar range. In parallel, we clarified their mode of action and developed a quantitative model that links the dynamic ligand-protein cross-talk to observed cellular and in vitro activities. Our results support the potential of using dynamicsbased approaches to develop original mechanism-based cancer therapeutics.Heat Shock Protein 90 (Hsp90) is a chaperone that controls th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…In the context of allosteric perturbation of PPIs, we characterized the effects of allosteric Hsp90 activators on its interactions in vitro, and on the stability of a number of its clients in cellular models: consistent with observations from other groups, administration of these accelerators induced a marked decrease in levels and viability of stringent client proteins of Hsp90 (for whose production Hsp90 is essential). This supports the concept that acceleration of conformational dynamics may in fact represent a new way of perturbing the chaperoning mechanisms that underlie cell viability: indeed, some of our allosteric compounds inhibit the proliferative potential of tumor cells, including those resistant to Hsp90 ATP‐competitive inhibitors …”
Section: Modulating Biological Functions By Targeting Protein–proteinsupporting
confidence: 68%
See 1 more Smart Citation
“…In the context of allosteric perturbation of PPIs, we characterized the effects of allosteric Hsp90 activators on its interactions in vitro, and on the stability of a number of its clients in cellular models: consistent with observations from other groups, administration of these accelerators induced a marked decrease in levels and viability of stringent client proteins of Hsp90 (for whose production Hsp90 is essential). This supports the concept that acceleration of conformational dynamics may in fact represent a new way of perturbing the chaperoning mechanisms that underlie cell viability: indeed, some of our allosteric compounds inhibit the proliferative potential of tumor cells, including those resistant to Hsp90 ATP‐competitive inhibitors …”
Section: Modulating Biological Functions By Targeting Protein–proteinsupporting
confidence: 68%
“…Comparative analyses of allosteric activators (Figure , left) and inhibitors (Figure , right) showed that the ligands induced different dynamics states and conformational ensembles in the protein, responsible for different functional responses . One of the Hsp90 activators is illustrated in Scheme (compound 26 ) …”
Section: Modulating Protein Functions With Allosteric Chemical Switchesmentioning
confidence: 99%
“…Therefore, developing non-ATP competitive compounds targeting Hsp90 deserves to be tested. In fact, quite a few of research works published during past several years indicate that the allosteric modulators binding to either the N-terminal domain or the interface region in between the middle domain and the C-terminal domain of Hsp90 might serve as new potential therapeutic opportunities (Bassanini et al, 2018;D'Annessa et al, 2017;Ferraro et al, 2019;Sattin et al, 2015;Yokoyama et al, 2015;Zierer et al, 2016;Zierer et al, 2014). Different from the working mode of the canonical ATP competitive inhibitors of Hsp90, the allosteric modulators target the non-canonical binding sites of the chaperone and induce activation of its ATPase activity (D'Annessa et al, 2017;Roe et al, 2018;Sattin et al, 2015;Yokoyama et al, 2015;Zierer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, quite a few of research works published during past several years indicate that the allosteric modulators binding to either the N-terminal domain or the interface region in between the middle domain and the C-terminal domain of Hsp90 might serve as new potential therapeutic opportunities (Bassanini et al, 2018;D'Annessa et al, 2017;Ferraro et al, 2019;Sattin et al, 2015;Yokoyama et al, 2015;Zierer et al, 2016;Zierer et al, 2014). Different from the working mode of the canonical ATP competitive inhibitors of Hsp90, the allosteric modulators target the non-canonical binding sites of the chaperone and induce activation of its ATPase activity (D'Annessa et al, 2017;Roe et al, 2018;Sattin et al, 2015;Yokoyama et al, 2015;Zierer et al, 2014). Meanwhile, although presenting accelerating effect on Hsp90's ATP hydrolysis activity, the application of these allosteric modulators would down-regulate the chaperoning function of Hsp90 for client proteins and cause cytotoxicity (D'Annessa et al, 2017;Ferraro et al, 2019;Sattin et al, 2015;Yokoyama et al, 2015;Zierer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation